1996
DOI: 10.5326/15473317-32-3-257
|View full text |Cite
|
Sign up to set email alerts
|

Canine mandibular osteosarcoma: 51 cases (1980-1992)

Abstract: Fifty-one dogs treated for mandibular osteosarcomas (OSs) were studied retrospectively. Treatments were partial mandibulectomy (n = 32); partial mandibulectomy and chemotherapy (n = 10); partial mandibulectomy and radiation therapy (n = 3); partial mandibulectomy, radiation therapy, and chemotherapy (n = 4); and radiation therapy alone (n = 2). The overall one-year survival rate was 59.3%. Dogs treated with surgery alone had a one-year survival rate of 71%, which is higher than the one-year survival rate for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
101
4
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 0 publications
4
101
4
3
Order By: Relevance
“…Vascular invasion was identified as present ¼ 1 or absent ¼ 0. Tumor type was identified as osteoblastic (OB), fibroblastic (FB), chondroblastic (CB), telangiectatic (TC), osteofibroblastic (OF), giant cell variant (GC), or osteochondrofibroblastic (OCFB) as described by Slayter et al 17 All samples were assigned a histologic grade of I, II, or III based on the histologic scoring and grading system defined by Straw et al 20 and summarized in Tables 1 and 2.…”
Section: Histopathology Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Vascular invasion was identified as present ¼ 1 or absent ¼ 0. Tumor type was identified as osteoblastic (OB), fibroblastic (FB), chondroblastic (CB), telangiectatic (TC), osteofibroblastic (OF), giant cell variant (GC), or osteochondrofibroblastic (OCFB) as described by Slayter et al 17 All samples were assigned a histologic grade of I, II, or III based on the histologic scoring and grading system defined by Straw et al 20 and summarized in Tables 1 and 2.…”
Section: Histopathology Datamentioning
confidence: 99%
“…Tumor grade, while prognostic in human osteosarcoma, 8 has historically not been consistently prognostic in studies of canine osteosarcoma with several studies showing no prognostic signifigance. 9,20 However, a recent study by Kirpensteijn et al showed a histologic grade of III to be an independent predictor of clinical outcome when cases of canine osteosarcomas from all locations in the body were evaluated. 11 The existence of a grading system that is significantly associated with survival for osteosarcomas, especially for this subset of osteosarcomas for which survival may be longer, would be invaluable for the clinical decision making process.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…No local recurrence or metastases were evident 21 months postsurgery. Straw et al 22 reported the use of Sm-153-EDTMP in 2 dogs with mandibular osteosarcoma. One dog was lost to follow-up at 41 months.…”
Section: Introductionmentioning
confidence: 99%